Effectiveness of Conterpressure Massage and Rebozo Technique on Reducing Pain In The First Stage Of Labor - Lina Marlina; Eneng Daryanti; Ai Rahmawati; Reni Nurdianti; Sri Gustini (HealthCare Nursing Journal, 2025)
Childbirth is a natural physiological process, but it can cause pain due to contractions. Labor pain if not treated can cause stress which can reduce uterine contractions. A midwife must be able to provide labor care that can provide comfort during labor, one of which is massage and rebozo. The purpose of this study was to determine the effectiveness of massage counterpressure andrebozo on labor pain. Method used quasi-experimental with a pretest-posttest, by comparing results between 2 groups, namely the massage groupcounter pressureand rebozzo technique. The study was conducted at BPM Bidan E, Tasikmalaya for 4 months from July to October 2024, population being all mothers giving birth in the first stage. The sample with quota sampling and each treatment being 15. Observation of pain using the Numeric Rating Scale (NRS) with 4 measurements during contractions every 30 minutes. The duration was 5-10 minutes. Analysis used Wilcoxon test. The results of the study were that counterpressure massage and rebozzo technique were effective reducing pain scale of the first stage labor. The results of the statistical test obtained p value = 0.352 (> 0.05), so that between massage counterpressure and rebozzo has no difference in reducing pain in the first stage labor. However, when viewed from the average difference in counterpressure massage is 2.67 while rebozzo the average difference is 2.22, so it can be stated that counterpressure massage more effective in reducing pain in the first stage than rebozzo. It is hoped that providers of labor care can reduce labor pain with various techniques according to the comfort of the mother giving birth.